Physical and Technological Principles of Processing Steel with UV Laser Radiation - Hnatenko, O. S.; Afanasieva, O. V.; Lalazarova, N. O.; Odarenko, E. N.; Sashkova, Y. V.; Ivanchenko, O. V.; Kurskoy, Yu. S. (СумДУ, 2023)
The main purpose of the article is to study the hardening of steel using non-standard wavelengths of laser radiation. The physical principles of the interaction of laser radiation with matter are also described. Experiments were carried out on hardening steel with a UV laser (wavelength 355 nm). The following experiments and a comparative analysis of volumetric hardening of steel with cooling in water, hardening with a YVO4 laser beam with (λ = 1.06 μm and hardening with a YVO4 laser beam with (λ = 0.355 μm. The studies were carried out on structural steel 45 and tool steels У12 and Р6M5. In the course of the research, new interesting scientific results were obtained: the study of the microstructure of U12 steel samples using an electron microscope showed that the martensite formed during quenching by UV radiation is more dispersed, as a result of which it can be concluded that such processing can lead to the production of surface nanostructures up to 100 nm in size. However, due to the low productivity and low power of UV radiation, the proposed steel hardening can be recommended for measuring and cutting tools.
Фізичні та технологічні принципи обробки сталі лазерним випромінюванням УФ-діапазону
Keywords: Microhardness; The Bouguer-Lambert law; Laser radiation; UV range; Microstructure; Nonlinear crystal; Laser beam; мікротвердість; закон Бугера-Ламберта; лазерне випромінювання; УФ-діапазон; мікроструктура; нелінійний кристал; лазерний промінь